2022
DOI: 10.1016/j.ultsonch.2021.105864
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasound pretreatment on the quality, nutrients and volatile compounds of dry-cured yak meat

Abstract: Highlights Ultrasonic treatment can improve dry-cured yak meat tenderness. Ultrasonic treatment accelerated lipid oxidation. Ultrasonic treatment had no effect on the TVB-N content. Ultrasonic treatment could significantly increase the essential FAA (EFAA). SFA content significantly increased with the increase of ultrasonic power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 57 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…Alves et al [9] also reported that the use of ultrasound (25 kHz, 128 W) treatment in manufacture of dry fermented sausages could significantly affect the proteolysis and formation of the volatile flavor compounds derived from lipid oxidation during the storage. Bao et al [10] showed the ultrasound pretreatment (300 W, 20 kHz) could significantly decrease the hardness of dry-cured yak meat by enhancing the muscle proteolysis. For these phenomenon, previously studies have underlined that ultrasound can positively interfere with the activity of protease and lipase, which can affect the muscle proteolysis and lipolysis [11] , [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Alves et al [9] also reported that the use of ultrasound (25 kHz, 128 W) treatment in manufacture of dry fermented sausages could significantly affect the proteolysis and formation of the volatile flavor compounds derived from lipid oxidation during the storage. Bao et al [10] showed the ultrasound pretreatment (300 W, 20 kHz) could significantly decrease the hardness of dry-cured yak meat by enhancing the muscle proteolysis. For these phenomenon, previously studies have underlined that ultrasound can positively interfere with the activity of protease and lipase, which can affect the muscle proteolysis and lipolysis [11] , [12] .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, there was no significant impact of HIU treatment on saturated fatty acid (SFA) and polyunsaturated fatty acid content. However, a study by Bao et al (2022) concluded that higher SFA content in dry-cured yak meat occurred from 400 W and the 20 kHz ultrasound application. They speculated that the cavitation effect of HIU application accelerated the oxidation of unsaturated fatty acids, and thus, ultimately, the SFA content tended to increase.…”
Section: Resultsmentioning
confidence: 98%
“…We speculated that the high concentration of umami-related compounds such as glutamic, glycine, and alanine affected higher umami intensity in cooked meat due to HIU application. To our best knowledge, only one study has reported lower glutamic, glycine, and alanine content corresponding to increasing ultrasound levels (0, 200, 300, 400 W) in yak semitendinosus muscle (Bao et al, 2022). The majority of studies have observed positive sensory effects in spite of the difficulty in analyzing different experiments due to differences in frequency, intensity, and time combinations used in sonicated treatments of meat.…”
Section: Sensory Attributesmentioning
confidence: 99%
“… Increase in tenderness, alcohols and aldehydes contents the appropriate ultrasonic power of 300 W particularly improves quality of dry-cured yak meat. [107] Uncured dry fermented beef Ultrasound cold bath; immersion in in acid whey environment (4 °C), 5 and 10 min sonication time 40 kHz, 480 kW, 10 min The effect of sonication on biogenic amine (BA) formation was investigated positive effect on retarding histamine (HIS), cadaverine (CAD), tyramine (TYR) and putrescine (PUT) formation the sonication treatment did not inhibit the growth of lactic acid bacteria (LAB) in dry-fermented beef [108] Beef jerky Ultrasonic bath systems, Lactobacillus sakei culture, 30 °C; 25, 33 and 45 kHz, 30 min sonication time They did not propose optimal conditions, Changes in fatty acid profiles were significantly affected by individual and/or interactive effects of L. sakei, drying time and ultrasonic frequency Changes in fatty acid profiles were significantly affected by individual effected of L. sakei , drying time and ultrasonic frequency. Interaction effect of ultrasound frequency with culture and drying time were more pronounced compared to individual effects.…”
Section: Ultrasound-assisted Fermentationmentioning
confidence: 99%